MUSTAHIQ ZAKAT PADI MENURUT PERSEPSI MASYARAKAT TOBING JULU KEC. HURISTAK KAB. PADANG LAWAS - Risalan Basri Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2018)
In carrying out the payment of rice farming zakat in Huristak District, Padang Lawas District, the farmers in giving their zakat determines the person who becomes mustahiq, usually is the fisabilillah category because that is what is usually there especially the amil that is officially determined does not yet exist. From the tradition that passed in the midst of the community where the farmers after giving their zakat to the mustahiq, then the mustahiq took their share 1/8 of the zakat they received, the rest handed back to muzakki to be used according to their needs. And usually if mustahiq does not give part of it back to the muzakkin, then mustahiq will become a chatter of people in the community and the simuzakki will not want to give zakat to him at the next harvest. The reason for mustahiq returning his zakat right to muzakki after taking it partially in the district Huristak Kab Padang Lawas. From each of the rice farmers who have the obligation to pay their income zakat (enough Nisab). mustahiq said that the zakat is only 1/8, while the rest is the rights of others who are stipulated by Allah in the Qur'an, because mustahiq cannot give to mustahiq which is partly returned to the muzakki so that it can be given to others